A PRELIMINARY ASSESSMENT OF THE EFFECTS OF DROUGHT ON WATER SUSTAINABILITY INDICATORS FOR NUCLEAR POWER GENERATION IN MONGOLIA - Ichinkhorloo Davaadorj; Eric Yee; Restu Maerani (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2019)
As the effects of climate change are being felt all over the world, sustainability indicators such as water withdrawn per kilowatt-hour, are becoming more important in the decision-making process for large infrastructure projects. In Mongolia, we are deciding whether to use nuclear as a main power source. However, local droughts in Mongolia can be quite severe, occurring every 4-5 years and several countries have shown droughts to interrupt their power plant operations. This study collects data and conducts analyses to estimate sustainability indicators for a nuclear power plant life cycle and extends these analyses to understand how an event such as a drought would affect such indicators. The first part of this study is to provide background information regarding life cycle water use from power generation facilities. Our study focused on the APR-1400 nuclear power plant. If we account for drought frequency in Mongolia, the life cycle water withdrawal is estimated to be approximately 7,611 L/MWh for the nuclear power plant.Keywords: nuclear, sustainability, water, drought